Pengaruh Pemberian dosis Pupuk P dan K Terhadap Pertumbuhan dan Produksi Bawang Merah (Allium ascalonicum L.) Varietas Bima - Irwansyah Ardianto Sinaga; Mahdaena Mahdalena; Hamidah Hamidah (Agrifarm : Jurnal Ilmu Pertanian, 2017)
The Effect of Dosage of P and K Fertilizer on Growth and Production of Red Onion (Allium ascalonicum L.) Bima Varieties. The purpose of this research is to know the influence of P and K fertilizer application and the interaction of the two treatments on the growth and production of shallot plant. The study was conducted for 3 months, ie from July to October 2016. The research site on land owned by UPTB Samarinda Agriculture Training Center East Kalimantan Province. This study used Randomized Block Design (RBD)  with a 3 x 4 factorial experiment consisting of 4 replications. The first factor is fertilizer fertilizer P which consists of 3 levels: namely p0 (without fertilization), p1 (fertilization 1 gr / plant), p2 (Fertilization 1.5 g / plant). The second factor is the dosage of K fertilizer consisting of 4 levels ie k0 (without fertilization) k1 (0.5 g / plant) k2 (1 g / plant) and k3 (1.5 g / plant). The result of this research showed that the treatment of P (P) fertilizer had significant effect on plant height 2 and 3 MST, wet bulb weight and dry bulb weight and no significant effect on plant height of 4 MST, number of leaves, and number of tillers. While the application of K (K) fertilizer had significant effect on plant height and leaf number at age 2 MST and no significant effect on height and number of leaf aged 3 and 4 MST, number of tiller, wet bulb weight and dry bulb weight. There was no interaction between P and K fertilizer application.